Implementation of SDGs in Primary Schools to Increase Environmental Awareness and Wellbeing through Education Quality Management - Bin Mahmudin Gagaramusu, Yusdin; zulnuraini; Kaharu , Sarintan Nurcahyati; Purbarani, Dyah Aini; Khairunnisa; Nazimuddin Al Kamil, Muhammad; Busthami Nur, Abdul Hamid (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Primary education plays a strategic role in supporting the Sustainable Development Goals (SDGs) agenda, especially in shaping environmental awareness and improving students' well-being from an early age. However, the integration of SDGs in learning practices still faces structural and pedagogical challenges at the school level. This study aims to examine the implementation of SDGs values in primary school learning and analyze how education quality management contributes to the effectiveness of the implementation. Method: This study used a qualitative approach with a collective case study design involving 15 primary schools in Palu City. Data were collected through observation, interviews and documentation, then analyzed thematically. Results: Results showed that schools with structured quality management systems and participatory leadership were more successful in internalizing SDGs values in learning, particularly through thematic activities and the Pancasila Student Profile Strengthening Project (P5). The impact is seen in the improvement of students' environmentally conscious behavior and social empathy. This research confirms the importance of a systemic approach that integrates pedagogical and managerial aspects in supporting the achievement of SDGs at the basic education level. Novelty: The findings contribute to the theory of sustainable education and offer practical implications for education policy at the local and national levels